Reading Biblical Narrative : A Practical Guide - Fokkelman, Jan P. (Tools for Biblical Study, 1999)
This is an enormously instructive and practical hands-on introduction for students of the Bible as literature, by one of the world's leading exponents of Hebrew narrative technique. Issues covered include: introduction to the art of reading, the narrator and his characters, narrative structure, narrative devices.